1985
DOI: 10.1007/bf01871091
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic regulation of basal and arginine vasopressin-stimulated hydraulic conductivity in rabbit cortical collecting tubule

Abstract: An extracellular adenosine responsive site that stimulates adenylate cyclase activity has been identified in several tissues. There is limited information on the presence and physiologic significance of adenosine receptors in well-defined segments of the mammalian nephron. We therefore examined the effect of adenosine and selected analogues on basal hydraulic conductivity in rabbit cortical collecting tubules (CCT) perfused in vitro. Adenosine and analogues with an intact ribose moiety produced a significant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…2 In the isolated, perfused rabbit collecting tubule, NECA has been shown to stimulate hydraulic conductivity. 90 Anand-Srivastava et al 91 demonstrated that NECA increases adenylyl cyclase activity in isolated segments of dog medullary thick ascending limb and collecting tubule. Furthermore, recent preliminary data indicate that adenosine A[ receptor activation results in a decrease in transtubular voltage in isolated cortical thick ascending limb, suggesting a direct action on sodium transport.…”
Section: Excretory and Tubular Epithelial Effects Of Adenosinementioning
confidence: 99%
“…2 In the isolated, perfused rabbit collecting tubule, NECA has been shown to stimulate hydraulic conductivity. 90 Anand-Srivastava et al 91 demonstrated that NECA increases adenylyl cyclase activity in isolated segments of dog medullary thick ascending limb and collecting tubule. Furthermore, recent preliminary data indicate that adenosine A[ receptor activation results in a decrease in transtubular voltage in isolated cortical thick ascending limb, suggesting a direct action on sodium transport.…”
Section: Excretory and Tubular Epithelial Effects Of Adenosinementioning
confidence: 99%
“…Elucidation of the renal tubular effects of adenosine is complicated by hormonally induced changes in hemodynamics and glomerular filtration rate that can mask direct effects of adenosine. Nevertheless, adenosine has been shown to antagonize vasopressin-stimulated water reabsorption in the cortical collecting duct (CCD)' (2) and inner medullary collecting duct (3), to stimulate Na+-phosphate and Na+-glucose transport in opossum kidney cells (4), and to inhibit the transepithelial voltage across isolated cortical thick ascending limbs of Henle's loop (5), suggesting a direct inhibitory action on sodium chloride reabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is involved in renal haemodynamics because it reduces renal blood flow (Hall et al, 1985;Arend et al, 1987;Gouyon & Guignard, 1989), in glomerular filtration rate (Churchill, 1982;Hall et al, 1985;Arend et al, 1987;Pawloska et al, 1987), in urine flow (Churchill, 1982;Dillingham & Anderson, 1985;Collis et al, 1986) and in sodium and potassium excretion rate (Churchill, 1982;Collis et al, 1986). Adenosine promotes glomerular constriction related to the entry of calcium into glomerular cells (Lopez-Novoa et al, 1987;Olivera et al, 1989).…”
Section: Introductionmentioning
confidence: 99%